Post-Traumatic Seizures - J Gordon Millichap (Pediatric Neurology Briefs)
Factors influencing the occurrence of post-traumatic seizures in 92 of 937 children with head injuries (9.8%) were studied in the Division of Neurosurgery, Children’s Memorial Hospital, Chicago, Illinois.